2013
DOI: 10.1371/journal.pone.0079957
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic DNA Vaccination of Vertically HIV-Infected Children: Report of the First Pediatric Randomised Trial (PEDVAC)

Abstract: SubjectsTwenty vertically HIV-infected children, 6–16 years of age, with stable viral load control and CD4+ values above 400 cells/mm3.InterventionTen subjects continued their ongoing antiretroviral treatment (ART, Group A) and 10 were immunized with a HIV-DNA vaccine in addition to their previous therapy (ART and vaccine, Group B). The genetic vaccine represented HIV-1 subtypes A, B and C, encoded Env, Rev, Gag and RT and had no additional adjuvant. Immunizations took place at weeks 0, 4 and 12, with a boosti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 35 publications
(56 reference statements)
1
15
0
Order By: Relevance
“…Because DNA vaccination can be repeatedly administered without development of immunity to the vector, repeated cycles of therapeutic vaccination resulted in a great benefit with a further reduction in viremia. Recent therapeutic trials using DNA vaccines showed improved immunogenicity ([ 207 , 208 , 209 , 210 ], for recent review see [ 211 , 212 ]) in agreement with findings of the macaque model. Thus, vaccination with plasmid DNAs has several advantages, including the possibility for repeated administration, and was shown to induce potent, efficacious, and long-lasting immune responses.…”
Section: Efficacy Of Dna Vaccine In the Macaque Modelsupporting
confidence: 70%
“…Because DNA vaccination can be repeatedly administered without development of immunity to the vector, repeated cycles of therapeutic vaccination resulted in a great benefit with a further reduction in viremia. Recent therapeutic trials using DNA vaccines showed improved immunogenicity ([ 207 , 208 , 209 , 210 ], for recent review see [ 211 , 212 ]) in agreement with findings of the macaque model. Thus, vaccination with plasmid DNAs has several advantages, including the possibility for repeated administration, and was shown to induce potent, efficacious, and long-lasting immune responses.…”
Section: Efficacy Of Dna Vaccine In the Macaque Modelsupporting
confidence: 70%
“…The vaccine was well tolerated, and there was no significant deterioration in clinical status, no occurrence of serious opportunistic infections, no evidence of adverse effects on the immune system, and no increase in viral replication in vaccinees. Up to 56% of the (94). Interestingly, vaccinated children developed higher lymphoproliferative responses to gag than did adults immunized with the same vaccine.…”
Section: Hiv Vaccine Responses In Infants and Adultsmentioning
confidence: 99%
“…Interestingly, increased anti-RT cellular reactivities were seen in some of the children (only seen in a minority of adults inoculated with the same vaccine). Therefore, potentially some children may have a better ability to react with viral rRT proteins than adults (56). Please see table 2.…”
Section: Cure Strategies and Potential Intervention Approaches In Pahmentioning
confidence: 99%